Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0117349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myopia and Its Risk Factors in Urban School Children in Delhi: The North India Myopia Study (NIM Study)

Abstract: PurposeAssess prevalence of myopia and identify associated risk factors in urban school children.MethodsThis was a cross-sectional study screening children for sub-normal vision and refractive errors in Delhi. Vision was tested by trained health workers using ETDRS charts. Risk factor questionnaire was filled for children with vision <6/9.5, wearing spectacles and for a subset (10%) of randomly selected children with normal vision. All children with vision <6/9.5 underwent cycloplegic refraction. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
185
9
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(238 citation statements)
references
References 30 publications
19
185
9
16
Order By: Relevance
“…Although a prior study in Delhi reported that children in the upper-middle socioeconomic status had a slightly higher risk of myopia, 26 we did not find any significant association between family economic status and myopia in children in this study. Mutti's study 13 using subjects from the Orinda Longitudinal Study of Myopia illustrated that the association between myopia and school achievement as measured by the Iowa Tests of Basic Skills may be weak.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although a prior study in Delhi reported that children in the upper-middle socioeconomic status had a slightly higher risk of myopia, 26 we did not find any significant association between family economic status and myopia in children in this study. Mutti's study 13 using subjects from the Orinda Longitudinal Study of Myopia illustrated that the association between myopia and school achievement as measured by the Iowa Tests of Basic Skills may be weak.…”
Section: Discussioncontrasting
confidence: 99%
“…32 In addition, after incorporating all the significant variables (eg, gender, age, outdoor activity, and parental myopia) in the two-level logistic regression models 2 and 3, the final results demonstrated that reading for pleasure more than 2 h per day (AOR = 1.84, 95% CI = 1.09-3.12) was only positively associated with myopia in boys, and spending time watching television per week was only positively associated with myopia in girls. These results were consistent with Saw's study 23 showing that students who read more than 2 h per day were more likely to be myopia, Ip's study 33 reporting that longer time spent on reading for pleasure was associated with a myopic refraction, and Saxena's study 26 illustrating that positive association of myopia was observed with children study/ reading more than 5 h per day, watching television more than 2 h per day, and playing computer/video games. In addition, although many previous studies revealed that the distance of near work was associated with myopia in children, some of these studies only consider the distance of close-up reading was an important risk factor for myopia, 33,34 and others regarded the distances of different near work activities as a composite variable (distance from near work) and roughly thought that a higher prevalence of myopia was associated with shorter near work distance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Prevalence of myopia was found to be 11.7%, showing a lower value than that of urban prevalence 13%. 6 In that girls were predominantly myopic when compared to boys, probably due to more time spent indoor, watching television, using mobiles, and habit of reading more books. According to International journal of health sciences survey among 4306 students, myopia was found in 4.74% of which 3.23% is contributed by girls.…”
Section: Discussionmentioning
confidence: 98%
“…Middle and Higher Secondary school was randomly selected and students of class 6 -12 were selected by Simple Random Sampling and students who were absent on the day of study and mentally challenged students were excluded from the study and the final study sample was of 854 students based on the previous prevalence of myopia 13% with absolute precision of 2.5%. 6 Students were explained about the study and after getting consent, a pilot study was carried out to standardize the study. Students were examined for refractive error by Snellen's chart and by non-cycloplegic auto refractometry and pinhole test.…”
Section: Methodsmentioning
confidence: 99%